Investigation of cultural beliefs of physical education teacher candidates with faculty of education - Huseyin Unlu; Mustafa Erbas; Yaprak Kalemoglu Varol (Selcuk University, 2014)
The purpose of this study is to adapt the Turkish version of Teacher's Cultural Beliefs Scale (OCDS) that is developed by Hachfeld et al (2011) that determines the cultural beliefs of teacher candidates, to determine physical education teachers' cultural beliefs and to compare physical education teacher candidates and other teacher candidates in terms of cultural beliefs and in addition, to examine cultural beliefs in terms of gender and grade variables in education. The research group consists of 330 teacher candidates in total that are educated at the faculty of physical education and training. As a data collection tool, OCDC and personal information form were used. In the analysis of research data, t-test and one way analysis of variance technique were used in order to determine the difference between descriptive statistics and dependent and independent variables. While there is not encountered significant difference (p gt;05) between arithmetic averages that are in attitude levels for cultural beliefs in terms of grade variables (p gt;.05), there is a significant differences in belief subscale and total scale for egalitarianism according to gender (p lt;.05). Besides, there are significant differences determined in attitudes towards cultural beliefs of teacher candidates of physical education and training faculties in terms of department variables (p lt;.05). Consequently, it was seen that the beliefs about multiculturalism and egalitarianism of physical education teacher candidates and other teacher candidates have been positive and as well as this, it was determined that other teacher candidates were at a higher level according to physical education teacher candidates.